COVID-19 in Solid Organ Transplant Recipients in Spain Throughout 2020: Catching the Wave?. Issue 10 (October 2021) - Coll, Elisabeth; Fernández-Ruiz, Mario; Padilla, María; Moreso, Francesc; Hernández-Vicente, Ana; Yañez, Iñigo; Molina, María; Vázquez-Sánchez, Teresa; Crespo, Marta; Facundo, Carme; Rodríguez-Ferrero, María Luisa; Ruiz Fuentes, María Carmen; et al.
Abstract : Background: Few studies have analyzed differences in clinical presentation and outcomes in solid organ transplant (SOT) recipients with coronavirus disease 2019 (COVID-19) across different pandemic waves. Methods: In this multicenter, nationwide, prospective study, we compared demographics and clinical features, therapeutic management, and outcomes in SOT recipients diagnosed with COVID-19 in Spain before (first wave) or after (second wave) 13 July 2020. Results: Of 1634 SOT recipients, 690 (42.2%) and 944 (57.8%) were diagnosed during the first and second periods, respectively. Compared with the first wave, recipients in the second were younger (median: 63 y [interquartile range, IQR: 53–71] versus 59 y [IQR: 49–68]; P < 0.001) and less likely to receive anti-severe acute respiratory syndrome coronavirus 2 drugs (81.8% versus 8.1%; P < 0.001), with no differences in immunomodulatory therapies (46.8% versus 47.0%; P = 0.931). Adjustment of immunosuppression was less common during the second period (76.4% versus 53.6%; P < 0.001). Hospital admission (86.7% versus 58.1%; P < 0.001), occurrence of acute respiratory distress syndrome (34.1% versus 21.0%; P < 0.001), and case-fatality rate (25.8% versus 16.7%; P < 0.001) were lower in the second period. In multivariate analysis, acquiring COVID-19 during the first wave was associated with an increased risk of death (OR: 1.47; 95% confidence interval [CI], 1.12-1.93; P = 0.005), although this impact was lost in the subgroup of patients requiring hospital (OR: 0.97; 95% CI, 0.73-1.29; P = 0.873) or intensive care unit admission (OR: 0.65; 95% CI, 0.35-1.18; P = 0.157). Conclusions: We observed meaningful changes in demographics, therapeutic approaches, level of care, and outcomes between the first and second pandemic waves. However, outcomes have not improved in the more severe cases of posttransplant COVID-19. Abstract : Supplemental Digital Content is available in the text.